Implementation of Low-Class Distance Learning (PJJ) at SD Negeri IV Samarang with The Objective of Maintaining Quality of Learning - Dani Gunawan; Elga Nadia; Eko Suryaningrat; Tetep Tetep (Institut Pendidikan Indonesia, 2022)
The quality of learning is determined by learning activities. This study aims to determine the implementation of low-grade distance learning (PJJ) at SDN IV Samarang with the aim of maintaining the quality of learning, including: 1. To find out lesson plans; 2. To find out the implementation of learning; 3. To know the evaluation of learning. The benefit of this research is to add scientific insight and a clearer theoretical/conceptual framework regarding the implementation of distance learning with the aim of maintaining the quality of learning. The research method used in this study is a qualitative research method with the type of document analysis research. The participants were low grade teachers, low grade students, and parents of low grade students. Data collection was carried out by analyzing documents, observations and interviews. Data analysis/processing is carried out by describing the state of the content/material, and looking for presentations on the quality of learning through the learning outcomes of low grade students in the form of pie charts in the implementation of distance learning. Based on the results of research that has been done by researchers, it can be concluded that: 1. The learning plan made before carrying out learning activities in PJJ is very good, this is evidenced by the learning plan that already fulfills the four elements that must exist in learning planning, namely; (1) there are goals to be achieved, (2) there are strategies to achieve goals, (3) resources that can support and, (4) implementation of each decision. 2. The implementation of distance learning, for the sake of the successful implementation of learning is quite good based on the learning components that have been implemented and are interrelated, namely: (1) teachers, (2) students, (3) learning materials, (4) learning methods, ( 5) learning media, and (6) learning evaluation. 3. Evaluation of distance learning is sufficient in its implementation involving the five principles of evaluation and their elements, namely schools, parents, the environment and society at large. As well as the learning outcomes shown by the value of 0-50, the percentage of Thematic, Mathematics, and B.Sunda scores obtained a percentage of 42%.